A STUDY ON THE STUDENT’S LEARNING STRATEGIES IN READING COMPREHENSION AT ELEVENTH GRADE OF IPS OF SMA TRI TUNGGAL PULAU BURUNG - Desmita Wulandari; Melda Yeni; Samsul Amri (J-Shelves of Indragiri (JSI), 2020)
The primary purpose of this study was to determine students' learning strategies in reading comprehension. This research was conducted at the eleventh grade of IPS of SMA Tri Tunggal Pulau Burung. This type of research is descriptive and uses total sampling techniques in determining research samples. This study's population was 53 students, and researchers took 30 students from them to be sampled in this study. Data collecting techniques use questionnaires from the questionnaire to find out the strategy in reading it. Then, this research shows that the value of students strategies in reading is mean values with result of cognitive strategies 37.93 % at Low category, metacognitive strategies 33.5 % at Low category, socio-affective strategies 33.2 % at Low category. From this study, it can be concluded that the students learning strategies in reading comprehension at the eleventh grade of IPS of Tri Tunggal Pulau Burung are in a low category. Findings showed that the students use cognitive strategies in reading comprehension at the eleventh grade of IPS of SMA Tri Tunggal Pulau burung.